2022
DOI: 10.1590/2177-9465-ean-2021-0302
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de quarta geração em Centro de Atenção Psicossocial Álcool e Drogas

Abstract: Resumo Objetivo Avaliar qualitativamente as ações ofertadas por um Centro de Atenção Psicossocial Álcool e Drogas na perspectiva dos familiares e dos usuários do serviço. Método Estudo qualitativo, do tipo estudo de caso, desenvolvido pelo método de avaliação de Quarta Geração, nos meses de setembro de 2019 a março de 2020. Os dados foram coletados por meio da observação e de entrevista aberta individual e analisados pelo Método Comparativo Constante. Os informantes foram nove familiares e oito usuários do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(25 reference statements)
0
2
0
2
Order By: Relevance
“…All professionals must interact with each other and with users, in an interdisciplinary and interprofessional way, to provide care in its entirety. However, there are many difficulties in carrying out this transition, especially with regard to the importance given to medicalization and medical care (14)(15) . The effectiveness of the psychosocial model determines the need for multidisciplinary work, in which each category uses the specific knowledge of its training to develop its actions (16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All professionals must interact with each other and with users, in an interdisciplinary and interprofessional way, to provide care in its entirety. However, there are many difficulties in carrying out this transition, especially with regard to the importance given to medicalization and medical care (14)(15) . The effectiveness of the psychosocial model determines the need for multidisciplinary work, in which each category uses the specific knowledge of its training to develop its actions (16) .…”
Section: Discussionmentioning
confidence: 99%
“…A study in a CAPS AD showed that users and families positively assess the guidelines offered by the team, highlighting the quality of information and the direction they receive (15) . In a child-juvenile CAPS, guidance to the family is understood as a facilitator of communication between the family and the team, when carried out with clarity and coherence with the demands (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Nela, todos os profissionais devem interagir entre si e com o usuário, de forma interdisciplinar e interprofissional, para realizar o atendimento em sua integralidade. No entanto, percebem-se muitas dificuldades para a realização desta transição, principalmente no que se refere à importância dada à medicalização e ao atendimento médico (14)(15) .…”
Section: Quando Chega Na Oficina Eles Perguntam O Que a Gente Quer Fa...unclassified
“…Estudo em um CAPS AD demonstrou que usuários e famílias avaliam positivamente as orientações ofertadas pela equipe, destacando a qualidade da informação e o direcionamento que recebem (15) . Em um CAPS infanto-juvenil, a orientação a família é entendida como facilitadora da comunicação entre ela e a equipe, quando realizada com clareza e coerência com as demandas (26) .…”
Section: Quando Chega Na Oficina Eles Perguntam O Que a Gente Quer Fa...unclassified